Comparative Analysis of Traffic State Estimation: Cumulative Counts-Based and Trajectory-Based Methods. Issue 1 (January 2015) - Tsubota, Takahiro; Bhaskar, Ashish; Nantes, Alfredo; Chung, Edward; Gayah, Vikash V.
The macroscopic fundamental diagram (MFD) relates space–mean density and flow. Because the MFD represents areawide network traffic performance, perimeter control strategies and networkwide traffic state estimation using the MFD concept have been studied. Most previous works used data from fixed sensors, such as inductive loops, to estimate the MFD, which can cause biased estimation in urban networks because of queue spillovers at intersections. To overcome this limitation, recent literature reported on the use of trajectory data obtained from probe vehicles. However, these studies were conducted with simulated data sets; few works have discussed the limitations of real data sets and their impact on variable estimation. This study compares two methods for estimating traffic state variables of signalized arterial sections: a method based on cumulative vehicle counts (CUPRITE) and one based on vehicle trajectory from taxi GPS logs. The comparisons reveal some characteristics of taxi trajectory data available in Brisbane, Queensland, Australia. The current trajectory data have limitations in quantity (i.e., the penetration rate), because of which the traffic state variables tend to be underestimated. Nevertheless, the trajectory-based method successfully captures the features of traffic states, which suggests that the trajectories from taxis can be a good estimator for networkwide traffic states.